Maksymos z Tyru, „O istocie boga według Platona” (XI) - Szarmach , Marian (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The paper contains a Polish translation of Maximus of Tyre’s Eleventh Discourse entitled Who is God according to Plato?, with a short introduction and notes.